Docking of urease with aspartic acid and urea - Muhammed Hamdan Shaikh (22415962) (2025)
I have investigated the inhibitory potential of L-aspartic acid against urease, an enzyme responsible pathological conditions such as peptic ulcers, urinary tract infections, and Nephrolithiasis. Using molecular docking approaches, The research demonstrate how L-aspartic acid binds effectively to the active site residues of urease, forming stable hydrogen bonds and electrostatic interactions. These findings provide novel insights into the potential of small natural amino acids Other Information License: http://creativecommons.org/licenses/by/4.0/